DIGITAL MARKETING IN PUBLIC INSTITUTIONS OF CULTURE AND ART IN THE REPUBLIC OF SERBIA (Heritage, 2022)
Social networks represent an indispensable aspect of digital marketing in modern business. Institutions of culture and art face daily challenges in order to offer the audience interesting content, which is the core of communication and promotion on digital platforms. Presence and activity on social networks have a positive impact on business, through quality content and direct communication with the audience, providing opportunities for improvement of business and attraction of new visitors. The aim of this paper is the investigation of the importance of digital marketing in the business environment of institutions of culture and art in the Republic of Serbia, with an emphasis on the institutions of culture and art of national importance, which were the subject of the analysis. Consulting the relevant literature enabled the presentation and definition of the theoretical framework of important concepts, in order to facilitate the understanding of the central part of the research. Based on the collected data and the insight into the current situation of accounts on social networks, the results that are offered show that Facebook, Instagram and YouTube are the most represented platforms in our country and as such, they are suitable starting points for forming a strategy of appearance on social networks, with the aim of increasing the number of followers and expanding potential visitors of cultural and artistic content. Clear formation of digital marketing strategy and determination in the application of its instruments is an area that provides an opportunity to improve business activities, with continuous education and training of marketing staff and expanding their competencies.
Keywords: digital marketing; institutions of culture and art; the Republic of Serbia; social networks